Cambrian rhynchonelliform nisusioid brachiopods: phylogeny and distribution. (21st March 2019) - Holmer, Lars E.; Kebria‐ee Zadeh, Mohammad‐Reza; Popov, Leonid E.; Ghobadi Pour, Mansoureh; Álvaro, J. Javier; Hairapetian, Vachik; Zhang, Zhifei
Abstract: A comprehensive review and phylogenetic analysis of genera and species presently assigned to the rhynchonelliform superfamily Nisusioidea and family Nisusiidae suggests that this short‐lived but important group of brachiopods first appeared in peri‐Gondwana during the second half of the Cambrian Series 2, before going extinct by the end of Drumian times. Nisusiides achieved their maximum morphological disparity and geographical distribution during the Wuliuan Age, and Laurentia was probably the major centre of their dispersal. A new phylogenetic analysis suggests an early separation of the lineages of spinose and non‐spinose nisusiids. The non‐spinose nisusiids probably evolved in Laurentia by the end of Cambrian Series 4. The new nisusiid genus Bellistrophia is described. The new species Nisusia multicostata represents the first documented rhynchonelliform (kutorginide) brachiopod from the Miaolingian (Drumian) of the Alborz Mountains, Iran.